SPATIAL TRANSFORMATION OF SURAKARTA’S PERIPHERAL RURAL VILLAGES UNDER IN-SITU URBANIZATION PHENOMENON : THE CASE OF GENTAN VILLAGE - Lia Sparingga Purnamasari; Galing Yudana; Erma Fitria Rini (Geoplanning: Journal of Geomatics and Planning, 2017)
Surakarta is one of the rapidly growing Indonesian cities. The pressure towards its peripheral area results in ‘in-situ urbanization’ phenomenon of its rural village surroundings. Gentan is one of Surakarta adjacent rural villages that has been undergoing rapid spatial transformation from rural to urban settlement in the last 20 years (1995-2016). This research aims to clarify the spatial transformation in Gentan village through examinations of its spatial elements on higher resolution level; (1) transformation of its street network connectivity, (2) land use pattern, (3) building density, and (4) public facilities and accessibility. Secondary data from satellite imagery and government institution and primary data from field survey were used in this research as sources. From Gentan’s spatial elements observations, this research concluded that this village was transforming into urban settlements by its spatial elements characteristics. Furthermore, this research provides interesting findings by its analysis on the neighborhood level that while Gentan was transforming into urban settlement, its internal connectivity was decreasing, residential uses dominated its land use, the village was dominated by the formal settlement, and the reach distance of its public facilities fluctuated across the time.